Towards an ontogenesis of queerness and divinity: queer political theology and "Terrorist assemblages" - Perry, Brock (Culture and religion, 2014)
The presumed categorical stability of sexual and national identities fuels a biopolitical phenomenon that Jasbir Puar has termed homonationalism. Critical responses to homonationalism must necessarily challenge the priority of ontological stasis that often characterises scholarly approaches to theorising both god and identity. This essay argues that a monotheistic political theology provides a basis for assuming notions of identity that are ontologically static. Post-secularity is put forth as an analytic for examining the intertwining of theological and cultural logics in the emergence of homonationalisms. Within that post-secular framework, affect theory is applied to analyse religion, nationalism and sexuality not as discrete social positions but as an assemblage of dynamic and interrelated multiplicities. This post-secular, affective approach allows for an expanded field of political and cultural analysis in queer theory and queer theology alike.